Depression 2017
DOI: 10.5772/66828
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lateralization of Emotional Processing in Depression

Abstract: There are three major hypotheses regarding the lateralization of emotion in the brainthe right-hemisphere hypothesis (RHH), the valence hypothesis, and the approachwithdrawal hypothesis. The approach-withdrawal hypothesis, which is the most widely accepted, states that emotions that elicit approach behaviors are lateralized to the left hemisphere, while emotions that elicit withdrawal behaviors are lateralized to the right hemisphere. In line with this hypothesis, it has been found that persons with depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…As recent evidence exists for the emotional lateralization in the brain, 34 our finding is logical in context of the theory that the right cerebral hemisphere is specialized for perception, expression, and experience of emotion. 35 As the cortico-ponto-cerebellar pathway connects the cerebral hemisphere with the contralateral cerebellum, 36 the left MCP lesions might have disrupted the cerebellar connectivity to the right cerebral hemisphere and consequently impaired patients experience and expression of depressive emotions in our cohort of patients.…”
Section: Discussionmentioning
confidence: 94%
“…As recent evidence exists for the emotional lateralization in the brain, 34 our finding is logical in context of the theory that the right cerebral hemisphere is specialized for perception, expression, and experience of emotion. 35 As the cortico-ponto-cerebellar pathway connects the cerebral hemisphere with the contralateral cerebellum, 36 the left MCP lesions might have disrupted the cerebellar connectivity to the right cerebral hemisphere and consequently impaired patients experience and expression of depressive emotions in our cohort of patients.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to note possible relation of between-eyes differences to hemispheric lateralization of valence processing as well as autonomic control. The most recent hypothesis regarding the lateralization of emotions is the approach -withdrawal hypothesis stating that the left prefrontal cortex is associated with intention, planning and regulation that are important for approach behaviors, whereas the right prefrontal cortex is linked to behavioural inhibition important for withdrawal (Pereira and Khan 2017). This hypothesis overlaps with the valence hypothesis reporting that regions of the left hemisphere are specialized for the processing of positive stimuli while processing of negative stimuli involves the right hemisphere (Davidson and Tomarken 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Although asymmetry is a common aspect of the human brain, asymmetry abnormalities are a condition that is particularly emphasized in MDD patients and can be demonstrated by MRI studies in some psychiatric disorders [8]. Studies conducted using neuroimaging techniques and designed on the basis of a hypothesis based on the relationship between emotions and brain lateralization have shown that structural and functional asymmetries between hemispheres can be found in MDD patients [9][10][11][12]. Numerous studies using neurocognitive, electrophysiological, and neuroimaging measurements in MDD patients provide evidence of functional brain asymmetry abnormalities [13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies using neurocognitive, electrophysiological, and neuroimaging measurements in MDD patients provide evidence of functional brain asymmetry abnormalities [13]. Although the hypothesis that many cognitive and emotional functions are performed asymmetrically between the left and right hemispheres has a long history, this hypothesis should still be evaluated [9]. Some researchers think that brain asymmetry reveals different clinical manifestations of different psychiatric disorders as a result of similar differences in brain function [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation